PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP KINERJA LINGKUNGAN BERBASIS PROPER PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Sari, Candra Widi; Ulupui, I Gusti Ketut Agung (Jurnal Ilmiah Akuntansi dan Bisnis, 2013)
ABSTRACT This study was an associative study aimed to find the influence of company’s characteristics such as profile, size, leverage, profitability, and growth on PROPER-based environmental performance. The research object was the PROPER-based environmental performance for period 2010-2012. The samples used were 18 companies with 54 financial statements. Samples were taken by purposive sampling method. Data collection techniques was using documentation. The analysis technique used was multiple linear regression. Based on the results of the analysis, it was found that profile, leverage, profitability and growth had no effect on the PROPER-based environmental performance. While size had a positive effect on the PROPER-based environmental performance. Keywords: company’s characteristics, environmental performance, PROPER